Investigation on the flexural properties and glass transition temperature of kenaf/epoxy composite filled with mesoporous silica for wind turbine applications - Tay, Chai Hua; Mazlan, Norkhairunnisa (Universiti Putra Malaysia Press, 2017)
This research investigates the strength of kenaf or epoxy composite filled with mesoporous silica and studies the hybrid effects between mesoporous silica orkenaf in epoxy matrix. The volume of kenaf woven mat is maintained constantly at 7.2vol%, whereas proportion of epoxy is varied with inclusion of mesoporous silica and silicon, keeping constant the volume of the composite at 67.5cm3. The proportion of mesoporous silica is altered from 0.5vol%, 1.0vol%, 3.0vol% and 5.0vol%, while silicon is kept constant at 3.0vol%. A total of 11 specimens were produced, each with its distinctive composition and mechanical strengths. Variation of fillers composition affects the mechanical strengths of the composite. SEM analysis shows that epoxy bonds well with silicon, kenaf and mesoporous silica. Some de-bonding among the components is observed within the composite although there is also some tearing of fibres and impregnation of epoxy within fibre, proving that the components have good interaction and do not act individually. Flexural test shows that mesoporous silica improves the flexural strength of the composite, where the highest value is 35.14MPa, obtained at 5.0vol% Mesoporous Silica in Kenaf/Epoxy (SiaK/Ep). It also improves the flexural modulus, where the highest value is 1569.48MPa, obtained at 3.0vol% SiaK/Ep. DMA result reveals that adding mesoporous silica increases the Tg of the composite produced. Highest Tg is obtained at 0.5vol% Mesoporous Silica in Kenaf/Epoxy modofied Silicon (SiaK/Ep-Si) with the value of 87.54°C.